Borderline tuberculoid leprosy: A manifestation of immune reconstitution inflammatory syndrome in a human immunodeficiency virus infected person - Mukhopadhyay Partha; Pal Shekhar; Mallik Sudeshna; Biswas Surajit; Saha Bibhuti (Wolters Kluwer Medknow Publications, 2006)
Immune reconstitution inflammatory syndrome describes a collection of inflammatory disorders associated with paradoxical deterioration of various pre-existing processes following start of highly active antiretroviral therapy (HAART) in human immunodeficiency virus (HIV)-infected patients. Leprosy as an opportunistic infection in immune reconstitution syndrome has been rarely reported in literature. A case of a 30-year-old HIV positive man with extrapulmonary tuberculosis of left foot on HAART having developed borderline tuberculoid leprosy as opportunistic infection in immune reconstitution syndrome has been reported.